Assessment of Secondary School Teachers’ Professional Development Programmes and Students Academic Performance in Selected Subjects in Enugu State - KANI, Sunusi Muhammad; EZEODO, Calista Chinwe (Ilorin Journal of Education, 2023)
This study assessed secondary school teacher’s professional development programmes and students’ academic performance in selected subjects. Descriptive survey design was used in the study. The population of the study comprised all secondary school teachers all secondary school teachers in Obollo-Afor education zone, Enugu State. Stratified simple random sampling technique was used to select 222 English, Mathematics, Physics, Chemistry and Civic Education from 634 teachers in the zone. Three research questions were formulated for the study. Instruments used in gathering data were Teachers’ Training programmes Checklist (TTPC) and Academic Performance Test. Data collected were analysed using percentage. The findings showed that the common profesional development programmes embarked by secondary school teachers includes evening courses, vacation and TRCN courses, workshops, correspondence courses and conferences; teacher’s professional development programmes positively influence student’s academic performance and improved the level of academic performance of students in English, Maths, Civic Education, Physics and Chemistry. The study concluded that the common profesional development programmes embarked by secondary school teachers includes evening courses, vacation and TRCN courses, workshops, correspondence courses and conferences. Teachers’ profesional development brings improvement in the level of academic performance of students in English, Maths, Civic Education, Physics and Chemistry. And thus, positively influences student’s academic performance. The study recommended among others that the government and other stakeholders in education should provide adequate profesional development opportunities for the teachers in secondary schools to improve and sustain students’ academic performance.